2015
DOI: 10.1063/1.4908040
|View full text |Cite
|
Sign up to set email alerts
|

Transition from diamagnetic to ferromagnetic state in laser ablated nitrogen doped ZnO thin films

Abstract: Transition from room temperature diamagnetic to ferromagnetic state in N doped ZnO (ZnO:N) films grown by pulsed laser deposition with tunable energy density has been identified. ZnO:N films deposited with moderate laser energy density of 2.5 J/cm2 are single phase and nearly defect free having N dopant substitution at O sites in ZnO lattice, exhibiting intrinsic ferromagnetism. When energy density reduces (<2.5 J/cm2), defects in ZnO:N film degrades ferromagnetism and exhibit diamagnetic phase when gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…65,66 On the basis of theoretical forecasts, N-ZnO based structures have also been considered as dilute magnetic semiconductors showing ferromagnetic interactions among nitrogen centers 67,68 and experimental observation of such a behaviour have already been reported in the literature. 69 Various techniques have been used to introduce nitrogen into the ZnO matrix, depending on the morphology of the bare system nitrogen has been successfully introduced in ZnO single crystals grown through a chemical vapor deposition process and successively annealed in a N 2 ow at high temperature (see below). ZnO nanorods have been produced on uorine tin oxide substrates and nitrogen has been introduced via ion implantation technique.…”
Section: N Doping Of Zinc Oxidementioning
confidence: 99%
“…65,66 On the basis of theoretical forecasts, N-ZnO based structures have also been considered as dilute magnetic semiconductors showing ferromagnetic interactions among nitrogen centers 67,68 and experimental observation of such a behaviour have already been reported in the literature. 69 Various techniques have been used to introduce nitrogen into the ZnO matrix, depending on the morphology of the bare system nitrogen has been successfully introduced in ZnO single crystals grown through a chemical vapor deposition process and successively annealed in a N 2 ow at high temperature (see below). ZnO nanorods have been produced on uorine tin oxide substrates and nitrogen has been introduced via ion implantation technique.…”
Section: N Doping Of Zinc Oxidementioning
confidence: 99%
“…Ambient pressures (100% O 2 ) were varied in the range of 1-100 mT to analyze the effect of growth kinetics on biosensing response. In our previous work, it has been reported that the laser fluence influences the defect profile in ZnO films, and native defects are maximum in ZnO thin films deposited at low laser energy density (1.0-1.5 J/cm 2 ) [17]. Since presence of defects in metal oxide matrix enhanced the electron communication property and are useful for obtaining good biosensing response characteristics [14]; ZnO thin films are grown at low laser fluence (1.2 J/cm 2 ) in the present work for biosensing applications [17].…”
Section: Immobilized Urmentioning
confidence: 99%
“…In our previous work, it has been reported that the laser fluence influences the defect profile in ZnO films, and native defects are maximum in ZnO thin films deposited at low laser energy density (1.0-1.5 J/cm 2 ) [17]. Since presence of defects in metal oxide matrix enhanced the electron communication property and are useful for obtaining good biosensing response characteristics [14]; ZnO thin films are grown at low laser fluence (1.2 J/cm 2 ) in the present work for biosensing applications [17]. Since the ablated species require minimum energy to settle down on the desired nucleating sites on the substrates, ZnO thin films were intentionally deposited without heating the substrates so that large number of defects may be introduced.…”
Section: Immobilized Urmentioning
confidence: 99%
“…This promoted search for DMS based on alternative dopants. Manifestation of RTFM has also been undertaken by doping with non-magnetic dopants such as H [26,[98][99][100][101][102][103][104][105][106][107][108][109][110]124,125], N [126,127], C [128][129][130][131], and S [47,78]. Interestingly, the observation of RTFM strongly suggests the presence of a spin-split band with a non-zero spin-orbit coupling in H-ZnO single crystals [100].…”
Section: Dopping With Non-magnetic Atomsmentioning
confidence: 99%